2016
DOI: 10.1161/jaha.116.003375
|View full text |Cite
|
Sign up to set email alerts
|

Role of Early Repolarization Pattern in Increasing Risk of Death

Abstract: BackgroundAn early repolarization pattern (ERP) has been hypothesized to be arrhythmogenic in experimental studies, but the prognostic significance of the ERP in the general population is controversial. We performed a meta‐analysis to examine the link between ERP and the risk of sudden cardiac arrest (SCA), cardiac death, and death from any cause.Methods and ResultsWe performed a literature search using MEDLINE (January 1, 1966 to July 31, 2015) and EMBASE (January 1, 1980 to July 31, 2015) with no restriction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
41
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(43 citation statements)
references
References 40 publications
2
41
0
Order By: Relevance
“…It is prevalent in 2.3% to 29.3% of the population depending on race, age and gender category [2,3]. Several recent reports and our previous studies indicated that ERP was associated with increased risk for ventricular fibrillation (VF) and sudden cardiac death (SCD) in the general population and in patients with structural heart disease [2,[4][5][6]. The 2015 ESC Guidelines for the management of patients with ventricular arrhythmias defined early repolarization syndrome (ERS) as the presence of ERP with resuscitation from a documented episode of unexplained VF or polymorphic ventricular tachycardia (VT) [7].…”
Section: Introductionmentioning
confidence: 99%
“…It is prevalent in 2.3% to 29.3% of the population depending on race, age and gender category [2,3]. Several recent reports and our previous studies indicated that ERP was associated with increased risk for ventricular fibrillation (VF) and sudden cardiac death (SCD) in the general population and in patients with structural heart disease [2,[4][5][6]. The 2015 ESC Guidelines for the management of patients with ventricular arrhythmias defined early repolarization syndrome (ERS) as the presence of ERP with resuscitation from a documented episode of unexplained VF or polymorphic ventricular tachycardia (VT) [7].…”
Section: Introductionmentioning
confidence: 99%
“…The critical role of the ER pattern in initiating ventricular fibrillation has been supported by observations of a consistent and marked J-wave accentuation preceding the onset of arrhythmia (1,10) and by electrophysiology (EP) mapping data that suggested an association between the origin of ectopy that initiated VF and the location of repolarization abnormalities (1). Meta-analysis on 16 studies involving 334524 subjects suggests that the ER pattern is associated with an increased risk for sudden cardiac arrest, cardiac death, and death from any cause (11). …”
Section: Introductionmentioning
confidence: 99%
“…Since then, the term “ER” has been ambiguously used to describe either of these ECG signs, perhaps due to the confusing inclusion of a “J” in both terms. Although these findings can theoretically coexist in some individuals, they should be considered separately .…”
Section: Early Repolarizationmentioning
confidence: 99%
“…In an attempt to summarize the large amount of data published since the first reports, Cheng et al . recently conducted a meta‐analysis of 16 studies and 334,524 subjects to examine the link between ER and the risk of SCD.…”
Section: Early Repolarizationmentioning
confidence: 99%